Faktor-Faktor yang Mempengaruhi Kecenderungan Fraud Akuntansi di Pemerintah Desa - Nisa’ Uzlifat Nashruah; Provita Wijayanti (Jurnal Akuntansi Indonesia, 2019)
This study aims to identify and analyze the effectiveness of internal control, ethical culture of the organization and individual morality on the occurrence of the accounting fraud tendency in the Government of Village / Sub District of Sayung.The population in this study is the village government in the District or Village of Sayung. The samples in this study used the Convenience Sampling Technique. The samples used in this study involved 40 respondents from 20 Sub District of Sayung. Data were collected through questionnaires and processed by means of multiple linear regression analysis test. The tests is by using SPSS for Windows version 16.0.The results of this study indicate that: (1) the variable of effectiveness of internal control has significant negative effect on the tendency of the accounting fraud in the Government of Village / Sub District of Sayung, (2) the variable of ethical culture of the organization has no significant effect on the tendency of the accounting fraud in Government of Village / Sub District of Sayung, (3) the variable of individual morality has significant negative effect on the tendency of the accounting fraud in the Government of Village / Sub District of Sayung.Keywords:     Internal Control, Ethical Culture of the organization, Individual Morality, Accounting Fraud Trends.